Exploring Pregnant Women's Experiences with RNN-Based Chatbot for Reproductive Health Education at Primary Health Centers: A Qualitative Phenomenological Study - Rahmat Rizki Siregar; Azhari Umar Siregar; Seri Astuti Hasibuan; Nurkholidah Nurkholidah; Desi Meliana Gultom; Evi Erianty Hasibuan (PT Inovasi Pratama Internasional, 2026)
Background: Inadequate reproductive health knowledge among pregnant women contributes to high maternal morbidity in Indonesia. Digital health promotion, particularly through recurrent neural network (RNN)-based chatbots, offers accessible and personalized health education. However, qualitative evidence on how such chatbots shape knowledge and experience remains scarce. Objective: This study aimed to explore pregnant women's experiences in acquiring reproductive health knowledge through RNN-based chatbot health promotion media at primary health centers, focusing on the depth and meaning of perceived knowledge change. Methods: A qualitative study with an interpretive phenomenological approach was conducted involving 24 pregnant women from two Puskesmas in Padangsidimpuan, Indonesia. Participants used the